Modification of χc1(3872) and ψ(2S) production in pPb collisions at √s NN = 8.16 TeV - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Cocha Toapaxi, Carlos; De Cian, Michel; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Langenbruch, Christoph; et al. (Physical review letters, 2024)
The LHCb Collaboration measures production of the exotic hadron 𝜒𝑐⁢1⁡(3872) in proton-nucleus collisions for the first time. Comparison with the charmonium state 𝜓⁡(2⁢𝑆) suggests that the exotic 𝜒𝑐⁢1⁡(3872) experiences different dynamics in the nuclear medium than conventional hadrons, and comparison with data from proton-proton collisions indicates that the presence of the nucleus may modify 𝜒𝑐⁢1⁡(3872) production rates. This is the first measurement of the nuclear modification factor of an exotic hadron.
Im Text ist "χc1" und "NN" tiefgestellt
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol
LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, C. Cocha Toapaxi, M. De Cian, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und viele weitere]
Gesehen am 13.05.2025